Two Cases of Severe Preeclampsia Were Diagnosed with HELLP Postpartum after Caesarian Section - Xuechuan Han; Yang Fan; Yan Yu (Hindawi Limited, 2014)
HELLP occurs in 0.5%-0.9% of all pregnancies. About 30% of the cases happen within 48 hours after delivery. Women with postpartum HELLP syndrome have significantly higher incidences of complications. Because of the absence of classical signs of preeclampsia, it can confuse physicians and lead to delay in diagnosis. Therefore, it is associated with serious maternal morbidity. We present two cases of acute postpartum HELLP syndrome after caesarean section following severe preeclampsia. Our cases were successfully managed with the timely diagnosis and therapy.